Կոմիտասի պարային ժառանգությունը - Գինոսյան, Գագիկ (Կոմիտասի թանգարան-ին-տ. հրատ.)
Հոդվածը նվիրված է Կոմիտասի ժառանգության ոչ այնքան հայտնի հատվածին: Առաջին անգամ Կոմիտասի պարային ժառանգությունն ինձ հետաքրքրեց «Հայ գեղջուկ պարը» և «Պարն ու մանուկը» աշխատությունները ուսումնասիրելուց հետո: Հետաքրքրությունս բազմապատկվեց, երբ տեղեկացա, որ պահպանվել է Կոմիտասի գրառած ութ պար, որոնք հետագայում տպագրվեցին «Կոմիտաս Վարդապետ. Ուսումնասիրություններ և Հոդվածներ» երկհատորյակի առաջին հատորում (2005): Համոզմունք դարձավ, որ գրառված պարերը պետք է վերականգնել և բարձրացնել բեմ, ներկայացնելով լայն հանրությանը: Խնդիրը բարդ էր նրանով, որ Կոմիտասի կողմից գրառված և նկարագրված պարերի հետ չի մատնանշվում, թե որ պարեղանակն է հանդիսանում տվյալ պարի մեղեդին: Ավելին, տպավորություն ունենք, որ նկարագրություններն ավարտուն չեն։ Վերականգնել ենք ութ պարերից երկուսը՝ համագործակցելով երաժշտագետների հետ, ինչպես նաև «Ինսթիգեյթ» ընկերության ինժեներների հետ։ Դիմել ենք նաև Սրբուհի Լիսիցյանի ստեղծած պարի գրառման համակարգին։ Впервые я обратился к наследию Комитаса после изучения работ “Армянский сельский танец” и “Малыш и танец”. Интерес возрос после того, как мне стало известно, что в музее Литературы и искусства им. Е. Чаренца хранятся рукописи записанных Комитасом восьми танцев. Мы были убеждены, что описанные танцы должны быть восстановлены, подняты на сцену и представлены широкой общественности. Задача осложнялась тем, что в описанных и записанных Комитасом танцах не указывается, какая именно мелодия представлена в данной танцевальной музыке. Более того, складывается впечатление, что описание незавершено. Нами было восстановлено два танца из восьми в сотрудничестве с музыкантами и инженерами компании “Инстигейт”. Обращались и к созданным Србуи Лисициан танцевальным записям. Надеемся, что в ближайшем будущем при поддержке музыковедов и наконец-то выйдет из тени оставшееся неисследованным наследие Комитаса, в том числе, и образцы танцев. This paper refers to the less known part of Komitas’s heritage. When starting my explorations on Komitas’s dances, I was initially astonished by two of his articles - the Armenian Peasant Dance and the Dance and the Child, which inform us how deep the author’s knowledge of the field was. Later, I found Komitas’s handwritings of transcriptions of eight Armenian dances in the Komitas Archive at the E. Charents Museum of Literature and Art (published in 2005, Komitas Vardapet, Studies and Articles, V. 1). Since then, I started purposefully working on those dances to introduce them also to the public as well as to confirm that discussing Komitas's work in ethnomusicology would be incomplete without considering his work on dances. The next stage of my work led to a number of challenges. First of all, Komitas described the dances without pointing out the exact melody to accompany the dance. Each time referring to this work, I was becoming more and more confident in the dance steps. However, a collaboration with a musicologist in Komitas's studies would be necessary. To my advantage was my previous two-decade experience of fieldwork in national dances and experience in reconstructing other dances transcribed by other dance-ethnomusicologists. Moreover, my experience in working with the system of Cynetograph (a system for recording dances, created by Srbuhi Lisitsyan, XX century) and the promotion of the Instigate computer programming company were helpful in my work. We succeeded in reconstructing two of Komitas's eight dances. In the case of Dances N1 and N6, we found the description of the dance in V. 10 of Komitas's Works, entitled Dance of the Pathway and Shoror. We found the corresponding melodies according to the descriptions of the dances. Those dances are now included in the repertoire of the Karin Folk Song and Dance Ensemble. Hopefully, the remaining samples of Komitas's dances will be reconstructed in the future as well.
Keywords: Թանգարաններ; Հայ երաժշտական ֆոլկլորագիտություն; Կոմիտաս Վարդապետ